Multiple-dose pharmacokinetics and pharmacodynamics of evogliptin (DA-1229), a novel dipeptidyl peptidase IV inhibitor, in healthy volunteers - Gu N; Park MK; Kim TE; Bahng MY; Lim KS; Cho SH; Yoon SH; Cho JY; Jang IJ; Yu KS (Dove Medical Press, 2014)
Namyi Gu,1,3,* Min Kyu Park,1,4,* Tae-Eun Kim,1,5 Mi Young Bahng,2 Kyoung Soo Lim,1 Sang-Heon Cho,1 Seo Hyun Yoon,1 Joo-Youn Cho,1 In-Jin Jang,1 Kyung-Sang Yu1 1Department of Clinical Pharmacology and Therapeutics, Seoul National University College of Medicine and Hospital, Seoul, Republic of Korea; 2Clinical Development Department, Dong-A ST Co, Ltd, Seoul, Republic of Korea; 3Department of Clinical Pharmacology and Therapeutics, Dongguk University College of Medicine and Ilsan Hospital, Goyang, Gyeonggi-do, Republic of Korea; 4Department of Clinical Pharmacology and Therapeutics, Dong-A University College of Medicine and Hospital, Busan, Republic of Korea; 5Department of Clinical Pharmacology and Therapeutics, Kunkuk University Medical Center, Seoul, Republic of Korea *These authors contributed equally to this work Purpose: Evogliptin (DA-1229) is a novel, potent, and selective dipeptidyl peptidase IV (DPP-IV) inhibitor in clinical development for the treatment of type 2 diabetes mellitus. This study aimed to investigate the pharmacokinetic and pharmacodynamic profiles and tolerability of evogliptin after repeated oral administration in healthy subjects.Patients and methods: A block-randomized, double-blind, placebo-controlled, multiple-dose, dose-escalation study was performed in a total of 30 subjects. Repeated once-daily doses of 5, 10, or 20 mg evogliptin or the same doses of placebo were orally administered to ten subjects in each dosage group for 10 days. Subjects in each group were randomized to receive evogliptin or placebo with a ratio of 8:2. Pharmacokinetics of evogliptin were evaluated, with its concentrations in serial plasma and urine samples collected following the first and last administrations. DPP-IV activity and glucagon-like peptide-1, glucose, and insulin levels were quantified to evaluate evogliptin's pharmacodynamics on the first and last dosing days.Results: All participants completed the study without any serious or severe adverse event. The evogliptin plasma concentration reached its peak within 4–5 hours and decreased relatively slowly, with a terminal elimination half-life of 33–39 hours. Repeated administration resulted in a 1.4- to 1.5-fold accumulation. Evogliptin's systemic exposure and inhibition of plasma DPP-IV activity increased in a dose-dependent manner. Inhibition of DPP-IV activity >80% was sustained over 24 hours in all evogliptin dose groups and provided an increase in postprandial active glucagon-like peptide-1 levels by 1.5- to 2.4-fold. Postprandial glucose levels in the evogliptin-treated groups were reduced 20%–35% compared to placebo, but were not accompanied by increased insulin levels.Conclusion: Repeated administration of evogliptin in healthy subjects was well tolerated and exhibited linear pharmacokinetics within the 5–20 mg dose range. A once-daily regimen of 5–20 mg evogliptin effectively inhibited DPP-IV activity.Keywords: DPP-IV, GLP-1, insulin, glucagon-like peptide-1, glucose